Security or Development: Which Drives the Other? Evidence from African Panels - BADRAOUI, Mhamed; ELOUAOURTI, Zakaria; BENNIS, Jaoud (Journal of Behavioral Economics and Policy, 2025)
This paper addresses the longstanding “chicken or egg” philosophical dilemma in the development-security field by analyzing the direction of causality between economic development and national security across African countries, with a particular focus on how this relationship varies by income level. To achieve this, we mobilized a dataset covering 33 African countries over the period 2004 to 2019, applying the Dumitrescu and Hurlin panel Granger causality test. Our findings reveal a robust, unidirectional causality from economic development to national security across all income levels, with the strongest effects in lower-income and lower-middle-income countries. Conversely, causality from homeland stability to economic development is only significant in upper-middle-income countries and weak or absent in others. These results suggest that while economic growth broadly drives homeland stability in Africa, the influence of national security on growth becomes significant primarily at higher income levels. Policy implications emphasize the need to promote inclusive and sustained economic growth to enhance national stability, especially in lower-income countries. Investments in infrastructure, education, and institutional quality are vital to support this growth and indirectly foster stability. For upper-middle-income countries, strengthening governance and political institutions is equally important to reinforce economic development. Our paper contributes to understanding the nuanced causal relationship between economic development and national security in Africa, highlighting the importance of income-level-specific strategies to achieve sustainable development and security.